A Critical Overview of Interleukin 32 in Leishmaniases - Ribeiro-Dias, Fátima; Oliveira, Iara Barreto Neves (Frontiers in Immunology, 2022)
Interleukin 32 (IL-32) has been investigated in several diseases due to its immune regulatory properties. It has been expressed in lesions of patients with American tegumentary leishmaniasis (ATL) and it is induced by New World Leishmania spp. that cause ATL and visceral leishmaniasis (VL). IL-32 can increase the inflammatory process through pro-inflammatory cytokine induction as well as to induce mechanisms by which parasites are killed. Genetic variants of IL-32 can be associated with resistance or susceptibility to ATL and different isoforms can be associated with distinct T helper lymphocyte profiles. This cytokine determines the transcriptional profile in bone marrow progenitor cells to mediate the trained immunity induced by -glucan and BCG, which contributes to resistance against Leishmania. IL-32 is need for vitamin D-dependent microbicidal pathway to parasite control. In this brief review, we will present the data obtained from human and murine studies on IL-32 in leishmaniasis, highlighting the current challenges to the understanding of the role of IL-32 in leishmaniasis.